Customer Management in the Energy Company - Zhang, Shijing; Sadílek, Tomáš; Čermáková, Elvíra; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2022)
The thesis first indicates the importance of customer relationship management. Literature review of customer loyalty, NPS, and IDIC model are included in the article. The examination of secondary data in order to determine NPS scores were researched. A satisfaction survey has been carried out for the main business sectors in order to make an effectively targeted customer strategy. The sample of data comprised 306 customers who met the criteria for the study. Study results may help the company to have a better market positioning through the IDIC model and provide petroleum station executives with insight into the effectiveness of the CRM in an effort to decrease costs and increase revenues.
Vedoucí práce: Tomáš Sadílek
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2022
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2022
Způsob přístupu: Internet
Keywords: international business [obor bakal. práce]; bakalářské práce; bachelor's theses